Development of a Human Antibody Tolerant Mouse Model to Assess the Immunogenicity Risk Due to Aggregated Biotherapeutics. Issue 10 (7th August 2013) - Bi, Vivian; Jawa, Vibha; Joubert, Marisa K.; Kaliyaperumal, Arunan; Eakin, Catherine; Richmond, Karen; Pan, Oscar; Sun, Jilin; Hokom, Martha; Goletz, Theresa J.; Wypych, Jette; Zhou, Lei; et al.
<x xml:space="preserve">Abstract</x> We describe a novel human immunoglobulin G2 (IgG2)‐tolerant and immune‐competent heterozygous mouse model (Xeno‐het) developed by crossbreeding a human Ig‐tolerized XenoMouse® with a C57BL/6J wild‐type mouse. The Xeno‐het mouse expresses both mouse and human immunoglobulin G (IgG) genes, resulting in B‐cells expressing human and mouse IgG, and secretion of human and mouse Ig into serum. This model was utilized to evaluate the immunogenicity risk of aggregated and chemically modified human antibodies. The mice were tested for their ability to break tolerance to self‐tolerant monomeric antibodies. Aggregates made by mechanical stirring elicited an anti‐drug antibody (ADA) response, but did not induce a robust and long‐term memory B and T‐cell response. Chemically modified antibodies made by oxidation were only weak and transient inducers of an immune response, as measured by a lack of both an ADA response and a B‐cell antigen‐specific response. Aggregate size was an important characteristic, as specific‐sized protein‐coated beads were able to elicit an immune response. We propose the use of this model to identify risk factors such as aggregation during manufacturing at early development for an increased potential immunogenicity risk. © 2013 Wiley Periodicals, Inc. and the American Pharmacists Association J Pharm Sci 102:3545–3555, 2013